POLITENESS STRATEGIES CONVEYED BY THE STUDENTS IN ONLINE DISCUSSIONS - Riris Handayani; Rachmawati; Tubagus Zam Zam Al Arif (Universitas Jambi, 2022)
The present research is inevitable revealing the politeness strategies conveyed by the students of English study program at Jambi University through online discussions. The data of the research are utterances of the research subjects (students) obtained from the students’ Whatsapp chat histories in Literature for Educational Purposes and Teaching English for Young Learners courses all through the classroom interactions. The technique of collecting the data is accomplished by means of reviewing the students’ chats as the consequence of online classes during the period of Covid-19. Every single word obtained from the students’ chats has been read conversely not all of the utterances are regarded as the data (data reduction process). The results of this research highlight four genuses of politeness strategies, namely positive politeness, negative politeness, bald on record, and off record. Briefly, the cultural issue entirely have the aftermath on the politeness strategies realized by the research subjects.